2003
DOI: 10.1021/ic034826o
|View full text |Cite
|
Sign up to set email alerts
|

[Mg(XeF2)n](AsF6)2(n= 4, 2):  First Compounds of Magnesium with XeF2

Abstract: The reaction between Mg(AsF(6))(2) and XeF(2) in anhydrous HF (aHF) at room temperature yields two compounds with XeF(2) bonded directly to the Mg(2+) cation: [Mg(XeF(2))(4)](AsF(6))(2); [Mg(XeF(2))(2)](AsF(6))(2). The 1:4 compound is obtained with excess XeF(2) while the 1:2 compound is prepared from stoichiometric amounts of Mg(AsF(6))(2) and XeF(2). [Mg(XeF(2))(4)](AsF(6))(2) crystallizes in an orthorhombic crystal system, space group P2(1)2(1)2(1), with a = 8.698(15) A, b = 14.517(15) A, c = 15.344(16) A, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 26 publications
3
39
0
Order By: Relevance
“…[9] Excess XeF 4 was used to favor the formation of a coordination compound. After the removal of excess XeF 4 under vacuum at room temperature, Raman spectroscopy of the product showed that XeF 4 was coordinated to the metal center.…”
Section: In Memory Of Neil Bartlettmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] Excess XeF 4 was used to favor the formation of a coordination compound. After the removal of excess XeF 4 under vacuum at room temperature, Raman spectroscopy of the product showed that XeF 4 was coordinated to the metal center.…”
Section: In Memory Of Neil Bartlettmentioning
confidence: 99%
“…The band at 575 cm À1 can be assigned to the vibration of the nonbridging XeF 2 ligand, as in the [Mg(XeF 2 ) 2 ](AsF 6 ) 2 compound. [9] The band at 460 cm Caution: Anhydrous hydrogen fluoride, AsF 5 , XeF 2 , and XeF 4 must be handled in a well-ventilated hood and protective clothing must be worn at all times! XeF 4 and all of its products are susceptible to moisture and they react with it forming XeO 3 , a compound which easily detonates.…”
Section: In Memory Of Neil Bartlettmentioning
confidence: 99%
“…A variety of the structures was found in this type of compounds: molecular structure (e.g. [Mg(XeF 2 ) 4 ](AsF 6 ) 2 [9]), dimer structure (e.g. [Cd 2 (XeF 2 ) 10 ](SbF 6 ) 4 [16], Fig.…”
Section: Review Of the Structures [M N+ (Xef 2 ) P ](Afmentioning
confidence: 99%
“…The first compound in which noble gas fluoride, XeF 2 , was observed to be bound directly to the metal center was [Ag(XeF 2 ) 2 ](AsF 6 ) [2]. In the last years, a whole series of the coordination compounds with XeF 2 as a ligand to the metal ion was isolated and many crystal structures of these compounds were determined [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The four XeF 2 molecules that form the non-capped face of the antiprism bridge Ca1 atoms to Ca2 atoms. The coordination sphere of the Ca2 atom is also an Archimedean [3] where more covalent character in the MÀF bond is expected (electron affinity of Mg 2+ is 15.04 eV, for Ca 2+ it is 11.87 eV [4] ). This situation means that the Lewis basicity of the fluorine atoms in the XeF 2 molecule strongly depends on the cation to which XeF 2 is already coordinated.…”
mentioning
confidence: 99%